Characterization of dumping soil and settlement prediction using Monte Carlo approach - Mohd Pauzi, Nur Irfah (2013)
Failures at the dumping sites are usually associated with settlement. Differential settlements of dumping soil cause leaking of methane gas to the air and infiltration of leachate to the river which are dangerous to human and environment. Settlement of dumping soil occurs for many years due to biodegradation process and creep. The behaviors of dumping soil are to be investigated and characterized so that the settlement could be predicted using Monte Carlo approaches. Dumping soil contains heterogeneous material such as concrete debris, decayed wood, clay, silt, sand and gravel. Dumping soil are characterize based on its characteristics such as Category I:soil like and non soil like, Category II: waste types and Category III: waste or soil. The importance of dumping soil characterization are that it helps the engineer to differentiate between soil and non soil like, the types of waste and to determine whether the soil mostly contains waste or soil. Settlement of dumping soil is very challenging to be evaluated and modeled since the settlement are non-uniform due to the different content of the soil. Waste materials were decomposed by the bacteria biodegrades the organic content in the waste would cause settlement. The settlement rate is assumed to be the amount of subsidence that is directly proportional to the amount of solids solubilized. Five settlement models used to calculate the settlement of dumping soil at Kuala Lumpur open dumping area were reviewed. These models are soil mechanics based model, Bjarngard and Edgers model, Power Creep function, hyperbolic function and rheological function. These five models are simulated using Monte Carlo approaches. Monte Carlo simulation is a method employed an algorithm that must be used with repeated random sampling of uncertainty for ca. 50-5000 number of iterations in order to obtain the parameters such as primary compression ratio (X), secondary compression ratio compressive stress X compressive stress(A) and ultimate settlement (Sult)of the soil at the dumping area. It is predicted that the final settlement of dumping soil can settled up to 20% to 30% of initial fill height. The expected outcome of the research is settlement prediction model of closed dumping area for post-development using Monte Carlo simulation. The predicted settlement by Monte Carlo simulation method could save time and cost. It could also be used by geotechnical engineers to determine the preliminary settlement. Moreover, it gives preliminary total settlement value for the design engineer and decision maker to decide on the remedial works and the depth of foundation level for post-development.